Nivel de conocimiento del síndrome coronario agudo en médicos residentes del servicio de emergencia del Hospital General Ambato del IESS - Laica Palate, Nelson Javier (2025)
Background: Ischemic heart disease is the leading cause of death worldwide; it causes approximately one in seven annual deaths in the United States. Acute coronary syndrome (ACS) involves a reduction in blood flow to the heart, causing damage to cardiac tissue. ACS is classified into unstable angina, non-ST segment elevation myocardial infarction (NSTEMI), and ST-segment elevation myocardial infarction (STEMI). The diagnosis of ACS is based on clinical, electrocardiographic, and enzymatic criteria. Management includes analgesics, anti-ischemic measures, antiplatelets, anticoagulants, and fibrinolysis therapy, both pharmacological and mechanical. Objective: To determine the level of knowledge about ACS among resident physicians in the Emergency Department of the General Hospital Ambato of IESS. Methods: A mixed-methods research study, both qualitative and quantitative, cross-sectional, descriptive, analytical, and observational, was conducted. A survey with a Cronbach's alpha of 0.81 was used, administered to 23 resident physicians, and included a questionnaire of 20 multiple-choice questions. Results: Three knowledge components were evaluated: concept and generalities, diagnosis, and treatment. The main findings were: 1) Knowledge of concepts and generalities: 65% good, 2) Diagnosis: 65% bad, and 3) Treatment: 70% bad. Conclusions: The level of knowledge about ACS among resident physicians in the Emergency Department of the General Hospital Ambato of IESS is average.